108 COMBATTING CONFUSION: SIMULATION-BASED MEDICAL EDUCATION FOR DEALING WITH DELIRIUM. (18th November 2021) - Duff, E; Moran, J; Doyle, M; O'Gorman, M; Ryan, M D; Finucane, P; Cooke, J; Pope, G; Mulcahy, R; O'Regan, N
Abstract: Background: Delirium is a complex, costly, and common clinical syndrome. Simulation-based medical education has been shown to be effective in enhancing the confidence, knowledge and skills of healthcare professionals in the management of delirium. We piloted an inter-professional education simulation on delirium in an acute hospital setting. The session's design was informed by participating in 'Sim Stars', a regional simulation development competition. Methods: We iteratively developed a low-fidelity simulation scenario on the recognition, prevention and management of delirium. The resulting simulation was piloted during an hour-long multidisciplinary departmental teaching session in a lecture hall setting. A candidate was asked to review an acutely confused patient (played by a 'confederate') on call. The candidate was expected to screen for delirium using the 4AT tool; assess for possible causes of delirium; and implement an appropriate management plan. After the session, qualitative feedback from the participants and audience was sought. Results: This pilot simulation included one candidate (medical Senior House Officer); two confederates (Consultant Geriatrician, Advanced Nurse Practitioner); two facilitators (Consultant Geriatrician, Advanced Nurse Practitioner); and an audience of 17 members. Feedback indicated that learners and trainers found this a helpful and enjoyable pedagogical method. Areas for improvement were highlighted, including providing advance notice for learners of the topic to be simulated; a more structured introduction defining the learning outcomes and declaring a 'blame free' environment; improved script for the patient confederate; and that having a team of learners (rather than specialists) to play 'confederates' may help improve team-building and reduce learner anxiety. Conclusion: This pilot simulation received positive appraisals from the team, and plans are underway to incorporate simulation more regularly into departmental teaching. Suggestions to improve future simulations were welcomed. Given its low-fidelity, this scenario can easily be used at any site for simulation-based training.